NILAI-NILAI SUBKULTUR DALAM MEREK MATERNAL DISASTER - Bastari, Rendy Pandita; Resmadi, Idhar; Lukito, Wahyu (Institut Bisnis dan Teknologi Indonesia, 2021)
Subculture is a movement against the mainstream that is manifested through music, fashion and lifestyle. One of the supporting element of the manifestation of a subculture is the existence of products from certain brands that have authenticity. The authenticity of a brand can be formed through the interaction of a brand with its community. A brand is not constructed by itself, but it must be built with various actions towards a community with its own ecosystem so as to give rise to consumer attitudes and habits towards a brand's product. Previous studies have shown that general consumers with subcultural actors show different attitudes towards a product from a certain brand. Another study shows that brands imitate the behavior patterns of a subculture and make it their target market to sell products. This study aims to take another approach, namely a sociological approach, by conducting a case study of a brand that is associative with a subcultural movement, one of which is Maternal Disaster. The method used in this study was an unstructured interview with the owner of the Maternal Disaster brand, visual samples analysis and an analysis based on the sociological theory of Pierre Bourdieu. The result of this research is a recommendation, brands that want to start moving in the subculture must prioritize the values ​​that are upheld by the subculture movement. In addition, interaction with the community must be built through the support of activities in the subculture.